Peningkatan Prestasi Belajar TIK Materi Microsoft Office Excel dengan Teknik Pembelajaran Model STAD pada Siswa Kelas VIII C SMP Negeri 2 Panggul - Wirawan, Surya Edi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this classroom action research is to find out objectively the improvement of ICT learning achievement in Microsoft Office Excel Materials through the Application of STAD Model Learning Techniques for Class VIII C Students in Semester 1 of the 2019/2020 Academic Year at SMP Negeri 2 Panggul Trenggalek. With this learning design, it is hoped that a student-centered learning atmosphere can be realized so that meaningful learning occurs with active, creative, effective students in a pleasant atmosphere. This research method is classroom action research with the Stephen Kemmis model. The STAD Model Learning Techniques learning is carried out in two cycles. The research results obtained include, among others, learning with Microsoft Office Excel material in Cycle I as follows. Grades that have been completed include a score of 100 for 3 children (11%), a score of 90 for 2 children (7%), a score of 80 for 3 children (11%), a score of 70 for 5 children (19%). Unfinished grades include: a score of 60 as many as 8 children (30%), a score of 50 as many as 3 children (11%) and a score of 40 as many as 3 children (11%). The average value of students in Cycle I is 67.41. While in Cycle 2 the results obtained are, the scores that have been completed include, the scores that have been completed include the value of 100 as many as 4 children (15%), the value of 90 as many as 5 children (19%), the value of 80 as many as 8 children (30% ), the value of 70 as many as 7 children (26%). Unfinished grades include: a score of 60 as many as 3 children (11%). The average value of students is 80.00. So there are already 85% or more students whose scores are above the KKM (70). This means that classically it has been completed because students who have reached the KKM have exceeded 85%. The results of this study, Cooperative Learning with STAD Model Learning Techniques can improve learning achievement in Microsoft Office Excel material for class VIII C students in Semester 1 of the 2019/2020 Academic Year.